Abaddon's Gate - Corey, James S. A. (Corey, James S. A. Expanse, 2013)
For generations, the solar system -- Mars, the Moon, the Asteroid Belt -- was humanity's great frontier. Until now. The alien artifact working through its program under the clouds of Venus has appeared in Uranus's orbit, where it has built a massive gate that leads to a starless dark. Jim Holden and the crew of the Rocinante are part of a vast flotilla of scientific and military ships going out to examine the artifact. But behind the scenes, a complex plot is unfolding, with the destruction of Holden at its core. As the emissaries of the human race try to find whether the gate is an opportunity or a threat, the greatest danger is the one they brought with them.